Internet meme as a means of intertextuality - Bulakh , Maiia (Current issues of Ukrainian linguistics: theory and practice, 2020)
The article considers the features of meme as a genre of Internet communication. The author focuses on the characteristics of the Internet meme as a means of intertextuality. The main attention is paid to the types and sources of intertextuality of memes in the Ukrainian-language Internet. In the last few years there has been a growing interest in study of new internet genres. To the author’s knowledge, Ukrainian internet meme has been scarcely investigated from the point of view of intertextuality. The relevance of this work is due to the fact that Internet memes in the Ukrainian media are insufficiently explored. In particular, the category of intertextuality of memes has been poorly studied. This paper presents a new look at a previously unexplored aspect of intertextuality in Internet memes of the Ukrainian-language segment of the Internet. The purpose of this article is to identify and describe the features of the implementation of intertextuality in Internet memes. The author defines the Internet meme as a unit of Internet discourse, which is characterized by a combination of standard in form and expression in meaning. In this paper, the scholar describes meme as an illustration and a text to it. Due to their nature, memes are concentrated information in a vivid form. The material for the study is Internet memes from social networks of the Ukrainian-language Internet, such as Facebook, Instagram, Twitter. In order to study intertextuality in internet memes the author uses intertextual analysis and continuous sampling method. This allowes to explore the intertextual basis of Internet memes. The research shows that the nature of the intertextuality of Internet memes is diverse. The author outlines that prototexts of Internet memes are precedent names, statements, texts and situations. The paper describes the types of precedent texts, as well as the mechanisms of intertextuality. The author separately considers the functions of precedent texts in memes. The results show that the main functions of Internet memes are a means of creating comic effect, popularization through introduction into the global context, aesthetic effect, concentrating information and intellectual play. Research on intertextuality in Internet memes appears fully justified as it is still insufficiently studied. The conclusions state that intertextuality is realized in Internet discourse, because Internet genres are interconnected and interactive. Duplication of the meme supports its precedent. Today, all texts on the Internet are interconnected by hypervocations, and the Internet has become one hypertext in the modern information and communication environment.